2008 IEEE International Symposium on Workload Characterization 2008
DOI: 10.1109/iiswc.2008.4636101
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating multi-core processor design space evaluation using automatic multi-threaded workload synthesis

Abstract: The design and evaluation of microprocessor architectures is a difficult and time-consuming task. Although small, handcoded

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…Table 1 summarizes which microarchitectural parameters can or cannot be changed during design space exploration without the need for recomputing the statistical profile. An important improvement over prior work in statistical simulation [6], [11], [13], [18], [19], [20] is that the cache statistics are largely microarchitecture-independent. As such, we can explore most of the memory hierarchy design space from a single statistical profile.…”
Section: Design Space Exploration Using Statistical Simulationmentioning
confidence: 97%
See 3 more Smart Citations
“…Table 1 summarizes which microarchitectural parameters can or cannot be changed during design space exploration without the need for recomputing the statistical profile. An important improvement over prior work in statistical simulation [6], [11], [13], [18], [19], [20] is that the cache statistics are largely microarchitecture-independent. As such, we can explore most of the memory hierarchy design space from a single statistical profile.…”
Section: Design Space Exploration Using Statistical Simulationmentioning
confidence: 97%
“…This paper considered multiprogram workloads only and showed that given the enhancements proposed in this paper, CMP resource sharing can be modeled accurately in statistical simulation for multiprogram workloads. Combining it with the Nussbaum and Smith [19] and Hughes and Li [13] approaches will make statistical simulation viable for modeling multithreaded workloads running on CMPs with shared resources. Second, this paper made a first but important step toward making the statistical profile microarchitecture-independent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce simulation overhead for CMP design, Genbrugge and Eeckhout proposed several statistical quantities to capture the behavior of cache access and shared resource contentions that are critical to the performance of multi-programmed programs running on CMPs [13,14]. Hughes and Li proposed to leverage statistical characteristics that capture the behaviors of memory sharing and inter-thread synchronization when constructing synthetic multi-threaded programs [16].…”
Section: Fast Simulation Techniquesmentioning
confidence: 99%